Images of Traditional and Modern Tuva in Ethnographic Cinema (based on the film of S. Rodnina and A. Menshov “Tyva Planet”) - Anisimov, Vladislav E.; Borisova, Anna S.; Kalinnikova, Ekatherina D. (The New Research of Tuva, 2022)
The article examines the audiovisual representation of the traditional and contemporary images of Tuva in ethnographic cinema, such as the film "Planet Tyva" (2019), directed by S. Rodnina and A. Men’shov at the request of the Russian Geographical Society.Visual and auditory means of representing elements of Tuvan ethnoculture are considered in the article as if the film was primarily a cinematographic text. Representing the image of Tuva, both visual and auditory units of this text are differentiated here into verbal and non-verbal ones.The visual non-verbal range takes the form of panoramic landscapes, as well as images of characters involved in religious practices or work. The visual verbal range mostly includes subtitled quotations from S.R. Mintslov’s "The Secret Mission: A Journey to Uryankhai" (1928), a book which forms the background of the film as its authors try to follow Mintslov’s route through Tuva. The book creates a canvas for the film narration and serve as a foil to compare the contemporary region and the long-gone "Mintslov’s Tuva".The audiovisual range of the film is represented by two categories of sounds: the diegetic (human speech, singing, musical motives, or sounds of nature) and extradiegetic (offscreen music, or spoken quotations from Mintslov's book) ones. Characters’ speeches in natural communicative situations are seen as the most representative among the auditory verbal tools, while the auditory non-verbal ones are vividly represented by ethnic music and sonic backgrounds of sounds of nature and everyday activities.The entirety of the cinematographic text aims to project a harmonious image of today's Tuva to the minds of mass audience of the film.
Keywords: Tuva; Tuvans; ethnographic cinema; cinematographic text; visual means; auditory means; ethnoculture; Tuvan culture